Management of the Online Single Submission–Risk-Based Approach (OSS-RBA) System at the Investment and Integrated One-Stop Service Office of North Minahasa Regency - Joseph, Daisy G.; Mamonto, Fitri H.; Tarore, Steven V. (JR Education, 2025)
Effective and efficient business licensing services are a primary requirement for improving the investment climate, especially for Micro, Small, and Medium Enterprises (MSMEs). The Indonesian government has implemented the Online Single Submission – Risk Based Approach (OSS-RBA) as a public service digitalization strategy aimed at simplifying the licensing process and enhancing legal certainty. However, the implementation of this system at the local level, including at the Investment and Integrated One-Stop Service Office (DPMPTSP) of North Minahasa Regency, faces several challenges such as low public understanding, limited infrastructure, and inadequate human resource competencies. This study aims to analyze the management of OSS-RBA in MSME licensing services at the DPMPTSP of North Minahasa Regency and to identify its supporting and inhibiting factors. The method used is a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Informants consist of DPMPTSP officials and business actors who are OSS-RBA users. The results indicate that although OSS-RBA provides convenience for MSMEs in obtaining a Business Identification Number (NIB) and shortens service time, its implementation is not yet optimal. Inhibiting factors include insufficient socialization, limited supporting facilities such as internet connectivity, and minimal personnel training. Meanwhile, supporting factors are the existence of clear regulations and the local government’s bureaucratic reform spirit. The discussion emphasizes the importance of system integration, capacity building for human resources, and the necessity of continuous monitoring and evaluation of the OSS-RBA system. In conclusion, OSS-RBA management at DPMPTSP North Minahasa is in a developmental stage but requires improvements in technical, structural, and HR aspects to become an effective instrument in public service and MSME empowerment.